Penyuluhan Kewirausahan: Peningkatan Skala Usaha UKM Kelompok Batik Giri Wastra Pura Girilayu Kecamatan Matesih Kabupaten Karanganyar - Kun Ismawati; Jani Kusanti; Giyono Giyono; Ambyah Atas Aji; Muflik Malikun; Savitri Savitri (Universitas Maritim AMNI Semarang, 2023)
Community service activities at the Faculty of Economics, University of Surakarta (UNSA) are intended to provide practical solutions for community entrepreneurship activities. This community service activity helps solve business management problems for the community; besides that it can provide practical knowledge to the public regarding the application of accounting economics through counseling activities. The community service held by the UNSA Faculty of Economics took place in Girilayu Village, Matesih District, Karanganyar Regency. The basic problem faced by partners is business management including financial management, human resources, and marketing. The results of this UNSA Faculty of Economics community service activity can help increase the professionalism of partner businesses and are expected to stimulate the growth of new entrepreneurs.